P316Expression and functional role of Ccdc80 in developing heart and in cardiomyopathies. (15th July 2014) - Iaccarino, D; Fedrigo, M; Castellani, C; Della Noce, I; Carra, S; Cotelli, F; Thiene, G; Angelini, A; Schepis, F
Abstract: Purpose: The gene Coiled Coil Domain Containing 80 (Ccdc80) is highly expressed in the hearts of vertebrates and its role is well defined in tumor suppression, glucose homeostasis and adipocyte differentiation. Our aims are to define its functional role during embryonic development and in cardiomyopathies. Methods: We used 3 different models: 1. Morpholino gene knock-down in Zebrafish to characterize Ccdc80 role in embryonic development; 2. Immunohistochemistry on heart ventricles from monocrotaline (MCT) injected rats (6 decompensated vs 6 normal animals); and 3. on human four chambers hearts from patients affected by dilated cardiomyopathy (DCM) (14 samples vs 2 controls from donor hearts which were not transplanted). Results: In Zebrafish Ccdc80 was widely expressed in the forming heart, during all the developmental stages and Ccdc80-morphants showed defects in the developing heart, with impaired cardiac looping, atrium enlargement, blood stasis and peripheral congestion (heart failure). These phenotypical alterations were due to a disorder of the late phase of cardiac development, after myocytes differentiation. MCT injected rats showed evident cytosplasmic overexpression of Ccd80 protein in hypertrophic right ventricles (high pressure overload site) in comparison to controls. Human samples from DCM patients showed cytosplamic overexpression of Ccdc80 protein particularly evident at the level of atria, where the staining pattern from mild and patchy in controls became strong and homogeneous in diseased hearts. Conclusions: Our results demonstrated that Ccdc80 has an important role for correct heart development in a model of vertebrates. In adult hearts under stress and/or pressure overload, Ccdc80 showed increased expression as a likely adaptive role to be further investigated.